2004
DOI: 10.1093/her/cyg127
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of the challenge of smoking cessation during pregnancy: a phenomenographic approach

Abstract: In general, most women are familiar with the need to stop smoking when they are pregnant. In spite of this, many women find it difficult to stop. Using a phenomenographic approach, this study explored Swedish pregnant and post-pregnant women's ways of making sense of smoking during pregnancy. A total of 17 women who either smoked throughout pregnancy or stopped smoking during pregnancy were interviewed. Five different story types of how they are making sense of smoking during pregnancy were identified: smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 25 publications
5
73
0
2
Order By: Relevance
“…13 A further study that demonstrated how women make sense of their smoking during pregnancy, concluded that women feel ashamed of their smoking and try to justify their smoking behaviour. 1,16 However, despite these negative emotions, smoking was still depicted as an essential daily coping mechanism. Furthermore, women lacked self confidence regarding their ability to maintain abstinence postnatally, which consequently decreased their motivation to attempt to quit during pregnancy.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…13 A further study that demonstrated how women make sense of their smoking during pregnancy, concluded that women feel ashamed of their smoking and try to justify their smoking behaviour. 1,16 However, despite these negative emotions, smoking was still depicted as an essential daily coping mechanism. Furthermore, women lacked self confidence regarding their ability to maintain abstinence postnatally, which consequently decreased their motivation to attempt to quit during pregnancy.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…1,12,13 Barriers to cessation, attitudes to nicotine replacement therapy (NRT) and perception of the counselling provided by health professionals were examined. 13,16 Cessation service provision was viewed negatively by women as they had previously been dealt with in a judgemental manner by health professionals and were therefore reluctant to discuss their current smoking behaviour.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations